Diari 1963-1977 - Dessì, Giuseppe (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2011)
This book is the fifth and last volume of the Diari of Giuseppe Dessí, a publication made possible by Franca Linari's transcription combined with the attentive editorship of Francesca Nencioni. The series began with the account of Dessí's early years (1926-1931) and continued with precious details of the period of his development (1931-1948) and the literary production of his maturity (1949-1951; 1952-1962). This time the author's experience and his own notes enable what is almost an 'autobiography of the artistic process' that offers eloquent insight into the creation of Paese d'ombre: not only a reconstruction of the genesis of the novel that won Dessí the Premio Strega, but also the sketching out of events and characters and the gradual definition of the plot. The literary evidence does not stop here, since significant texts of his theatrical production (Eleonora d'Arborea) can also be placed in this last fifteen years, along with narrative (for example Lei era l'acqua). All is set against the backdrop of family, friends (who also suddenly disappear), political passion and a courageous struggle against disease.